(untitled) (translation. a transdisciplinary journal, 2022)
The central problem of today’s global interactions is the tension between cultural homogenization and cultural heterogenization. (p. 32) […] For polities of smaller scale, there is always a fear of cultural absorption by polities of larger scale, especially those that are nearby. One man’s imagined community is another man’s political prison.